Arabic Alphabet Learning Media Innovation in Increasing Learning Interest in BTQ Lessons for Grade 2 Students of SDN Purwodadi I - Julaikha, Siti; Saifulah, Saifulah; Marzuki, Ahmad; Sholikhudin, Anang (Literacy: Journal of Education and Social Science, 2024)
The learning media in the introduction of hijaiyah letters at SDN Purwodadi I is still not interesting for students, so that students are bored and have difficulty understanding hijaiyah letters. With these problems, the researcher aims to innovate learning media that is fun and makes it easier for students to understand hijaiyah letters. Therefore, here the researcher will analyze and describe (1) the innovation of Arabic alphabet learning media in BTQ lessons, (2) the feasibility of Arabic alphabet learning media in BTQ lessons, (3) the increase in learning interest in BTQ lessons with Arabic alphabet media. The type of research used is R&D with the ADDIE model, namely, Analysis, Design, Devolepment, Implement, Evaluation. The techniques carried out in data collection are by means of observation, interviews, questionnaires, and documentation. The results of this study show that the feasibility of Arabic alphabet learning media from the assessment of material expert validators is 3.5 with a very feasible category, and the results of the media expert validators are 3.5 which means very feasible as well, while the observation results sheet on students in knowing hijaiyah letters is 85% with a very high category. It can be concluded that the learning media that has been made by researchers is very feasible to use because it has achieved the indicators achieved.